Minimal Bactericidal Concentration for a Quaternary Ammonium Compound used in Soak Liquors - (:unkn) unknown (SOC LEATHER TECHNOL CHEMISTS, 2013)
The soaking process is an ideal environment for bacterial growth and bacterial activity during this process causes severe damages on hides. The use of an effective bactericidal agent during soaking is very important to prevent the detrimental effect of bacteria on hides. A quaternary ammonium compound (QAC) containing 12.5% didecyl dimethyl ammonium chloride and 12.5-% benzyl dimethyl ammonium chloride which is used in soaking liquors in Turkiye was examined for its effect on Bacillus licheniformis, Bacillus pumilus, Staphylococcus intermedius, Pseudomonas luteola, Enterobacter cloacae, Vibrio fluvialis and Enterococcus faecium. Staphylococcus intermedius, Pseudomonas luteola, Enterobacter cloacae and Enterococcus faecium were isolated from soak liquor containing 0.8g/L of the test agent. Bacillus licheniformis, Bacillus pumilus and Vibrio fluvialis were isolated from salt-pack-cured hides. These bacteria were commonly found in isolates from salted hides. The effect of the test agent at different concentrations on the bacteria was examined by the Kirby-Bauer disk diffusion method on Mueller Hinton Agar both at 25 degrees C and at 37 degrees C. In addition, the Minimal Bactericidal Concentration of the agent for the bacteria and the mixed population of these bacteria was also determined in Mueller Hinton Broth at 37 degrees C. All concentrations of the agent produced an inhibition zone for all of the test bacteria. Inhibition zone diameter changed according to concentration of agent and the species of bacteria. The agent was found to be more effective at 25 degrees C than at 37 degrees C. 2.97g/L of the agent in Mueller Hinton Broth was found to kill both the bacteria and mixed culture at exposure times of both 8 and 24 hours at 37 degrees C. It was concluded that the agent should be used in higher concentrations in soak liquors to inactivate the bacteria that might cause major damages on hides.
Keywords: PACK CURED HIDES; DIDECYLDIMETHYLAMMONIUM CHLORIDE; LEATHER; PRESERVATION; SKINS; SALT; FLOAT